Depression Management by NICU Nurses: Mothers' Views. (June 2016) - Segre, Lisa S.; Orengo-Aguayo, Rosaura E.; Siewert, Rebecca Chuffo
The purpose of this article was to evaluate attitudes of mothers of newborns hospitalized on the neonatal intensive care unit (NICU) toward nurse-delivered depression screening and counseling. NICU mothers ( N = 200) completed questionnaires assessing their views toward being screened for depression by nurses, treatment provider preference, and interest in learning about Listening Visits (LV), a nurse-delivered intervention. The views of 23 LV recipients were also assessed. Most mothers were receptive to depression screening by nurses, two thirds would see a nurse for counseling, and half were interested in learning more about LV. Among LV recipients, half readily embraced the idea and the remaining recipients were skeptical but opted to try. After receiving LV, recipients unanimously rated LV and the skill of the LV provider highly. Screening and counseling by NICU nurses could increase detection of depression and treatment use among at-risk women. Assessing nurses' perspectives about implementing this model of care is an important future research direction.